THE INFLUENCE OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION ON EMPLOYEES AT CV KURNIA FITRI AYU FARM - Moh Askiyanto; Elly Lestari; Muhammad Mukid (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
This study aims to determine the influence of work motivation and discipline through job satisfaction. This research was conducted offline using questionnaires distributed to various respondents in CV Kurnia Fitri Ayu Farm, totaling 33 people based on the saturated sample formula. The quantitative Approach is the method used in this study. The presence of working variables makes Path Quality Analysis an appropriate research analysis. Research results Model I Partially know that work motivation has a significant effect on job satisfaction and work discipline has a significant effect on job satisfaction. For Model II, it is known that work motivation has a significant effect on employee performance, work discipline has a significant effect on employee performance, and job satisfaction has a significant effect on employee performance. The indirect effect of the relationship between work motivation and Employee Performance is not able to mediate Job Satisfaction, and the indirect effect of the relationship between work discipline and Employee Performance is also not able to mediate Job Satisfaction.